Physicians’ and Nurses’ Perceptions Regarding Disclosure of Patient Safety Incidents - Majeed, Rawan Ahmad; Qattan, Ameerah (Journal of Ecohumanism, 2024)
Patient safety is central to healthcare quality, yet the disclosure of patient safety incidents (PSIs) remains a complex challenge. This study explores the perceptions of physicians and nurses at Al-Noor Specialist Hospital, Saudi Arabia, regarding PSI disclosure. Using a cross-sectional descriptive design, data were collected via a survey distributed to 436 participants, including 272 nurses and 164 physicians. Findings emphasize the importance of clear protocols and training for PSI disclosure, and the role of organizational culture in fostering transparency. Insights from this study can inform strategies to improve PSI disclosure practices and patient trust.